Official Financing for Developing Countries 1997. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This study provides information on official financing for developing countries with the focus on low and lower-middle-income countries. It updates the 1995 edition and reviews developments in direct financing by offical and multilateral sources. Topics of interest include external debt sustainability for heavily indebted poor countries; new official financing flows to developing countries; developments in export credits;financing from multilateral institutions; debt restructuring by official bilateral creditors; plus, numerous appendices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet